Pengaruh Penggunaan Bahan Ajar "KOPER" Berbasis RME Terhadap Peningkatan Kemampuan Pemahaman Konsep Matematis Siswa SD Fase B - Rosita, Rosita; Robandi, Babang; Mufliva, Rosiana (Griya Journal of Mathematics Education and Application, 2025)
This research is motivated by the problem of the low level of mastery of mathematical concepts regarding multiplication of whole numbers up to 100 in elementary school students in phase B. Based on the findings of an initial study conducted in an elementary school, as well as the results of a review of various previous studies, it was found that one of the causes was the learning process that had not integrated the use of contextual and relevant learning materials to students' lives. To overcome this problem, it is necessary to have teaching materials based on a mathematical approach, namely the RME-based "KOPER" learning material which is made for the material on multiplication operations of whole numbers up to 100. The choice of the word "KOPER" is taken from the syllables contained in the sentence "Multiplication Concept" which is the content of the learning material which is adjusted to the principles of the RME approach. This study aims to examine whether the implementation of RME-based “KOPER” learning materials has an effect on improving the ability to understand mathematical concepts of elementary school students in Phase B, in the topic of multiplication of whole numbers up to 100. The research method used is quantitative with a quasi-experimental design in the form of a non-equivalent control group design. The subjects of this study were third-grade elementary school students, divided into two groups: a control group and an experimental group, each consisting of 20 students. Data collection was carried out using test instruments in the form of pre-tests and post-tests. The results of this study indicate that the implementation of the “KOPER” learning material oriented towards Realistic Mathematics Education (RME) has an effect on improving students' ability to understand concepts, especially the multiplication material in elementary school students in phase B.